Increased concentration of circulating calcitonin gene related peptide during normal human pregnancy. Issue 6558 (22nd November 1986) - Stevenson, J C; Macdonald, D W; Warren, R C; Booker, M W; Whitehead, M I
Abstract : Calcitonin gene related peptide is an extremely potent vasoactive peptide that causes profound vasodilatation in man. Its distribution in perivascular nerves suggests that one of its functions may be the regulation of peripheral vascular tone. Pregnancy is a physiological condition in which there are major haemodynamic changes. An increase in plasma volume of about 40% necessitates changes in peripheral vascular tone. In a cross sectional study plasma concentrations of immunoreactive calcitonin gene related peptide were measured throughout normal pregnancy and at five to seven days post partum. Calcitonin gene related peptide concentrations were significantly increased throughout pregnancy but fell after delivery. Calcitonin gene related peptide may participate in the physiological regulation of vasomotor tone in man.